Linear Trend Application on the Estimated Age of Distribution Transformer Based on the Load Growth and Environmental Temperature - Azhar, Fadly; Rahmawati, Yuni; Fadlika, Irham (Frontier Energy System and Power Engineering, 2019)
This research aimed to find the age loss of distribution transformer based on the load growth and ambient temperature to predict the remaining age of the transformer. This research used the remaining estimation age calculation based on load growth that was predicted using the linear trend analysis. The distribution transformer in this research was the BO043 200 kVA, installed in 2012, and was operated in Bolo Feeder, Woha District, Bima Regency. The results showed that the BO043 transformer was operating at the average ambient temperature of 28â„ƒ with the optimum loading threshold of 92.77% from its power rating. The transformer would experience age reduction if the load given were above that value. The calculation results showed that the BO043 transformer had the estimated remaining age of 4 years from the standard 23 years with the 2019 load prediction of 83.39% and up to 115.94% load prediction in 2022.